The Effect of Ajwa Dates (Phoenix dactylifera L) Consumption to Antral Ovarium Imaging by with Ultrasonography (USG) Transvaginal of Perimenopausal Women - E, Syahril; N A, Mappaware; F E, Mulyadi (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: Perimenopause is a transition from the reproductive period to the menopause stage with a decrease in the number and function of oocytes. Transvaginal ultrasound is a reliable alternative method for detecting ovarian reserve. Ajwa dates contain phenolic and other flavonoid components which are considered to have the potential to improve the ovarian condition of perimenopausal women which can be assessed by increasing the number of antral follicles as measured by transvaginal ultrasound. This study aims to determine the effect of consuming ajwa dates (Phoenix dactylifera L.) on the appearance of ovarian follicles using transvaginal ultrasound in perimenopausal women. Methods: This research is a quasi-experimental study with a pre-post control design carried out at RSIA Sitti Khadijah I Muhammadiyah Makassar, South Sulawesi, Indonesia, from May to September 2023. This research involved 44 perimenopausal subjects aged 42-48 years who were divided into 2 groups randomly (28 intervention groups, 16 control groups). Subjects in the intervention group consumed seven pieces of ajwa dates (60-70 grams each seven pieces) every morning before having breakfast for eight weeks. The transvaginal USG was performed twice, the first was on day three of the menstrual cycle of each subject and the second was after eight weeks of intervention. A comparison of changes in ovarian follicles was analyzed using the Mann-Whitney U test. Results: This study showed a significant decrease in the number of antral follicles in the intervention group and an increase in the number in the control group (p<0.05). Meanwhile, the size of the antral follicles showed a significant increase in the intervention group and a significant decrease in the size of the antral follicles in the control group (p<0.05). Conclusion: Consuming Ajwa dates as an exogenous antioxidant can affect the number and size of antral follicles, which is an indicator of improving the condition of perimenopausal women's ovaries. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S66